Neurodevelopmental delay with critical congenital heart disease is mainly from prenatal injury not infant cardiac surgery: current evidence based on a meta‐analysis of functional magnetic resonance imaging. (June 2015) - Li, Y.; Yin, S.; Fang, J.; Hua, Y.; Wang, C.; Mu, D.; Zhou, K.
ABSTRACT Objective No consensus has been reached regarding whether brain injury related to congenital heart disease (CHD) is caused by infant cardiac surgery and/or prenatal injury resulting from the CHD. We performed this meta‐analysis to identify the likely cause of neurodevelopmental delay in CHD patients. Methods We carried out a literature search without language restriction in December 2013, retrieving records from PubMed, EMBASE, the Cochrane Library and the World Health Organization trials center, to identify studies applying functional magnetic resonance imaging (fMRI) evaluation of brain function before surgery and, in some cases, after surgery (both immediate term and short term postoperatively). The preoperative and postoperative fMRI results were extracted, and meta‐analysis was performed using Revman 5.1.1 and STATA 11.0, according to the guidelines from the Cochrane review and MOOSE groups. Results The electronic search yielded 937 citations. Full text was retrieved for 15 articles and eight articles (nine studies) were eligible for inclusion: six studies (n = 312 cases) with fMRI analysis before surgery and three (n = 36 cases) with complete perioperative fMRI analysis. The overall average diffusivity of CHD cases was significantly higher than that of controls, with a summarized standard (std) mean difference of 1.39 (95% CI, 0.70–2.08), and the fractional anisotropy was lower in CHD cases, with a summarized mean difference of −1.43 (95% CI, −1.95 to −0.91). N‐acetylaspartate (NAA)/choline (Cho) for the whole brain was significantly lower in CHD cases compared with healthy ones, while lactate/Cho was significantly higher in CHD cases. Immediate term postoperatively, significant changes in NAA/creatine and NAA/Cho, relative to preoperative values, were found. However, the difference did not persist at the short‐term follow‐up. Conclusion This meta‐analysis suggests that the delay in neurological development in newborns with CHD is due mainly to prenatal injury, and cardiac surgery might lead to mild brain injuries postoperatively, but fMRI shows recovery within a short period. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.